Research on mechanical analysis and optimal design of electromagnetic variable pre-pressure ultrasonic motor - Ruikun Niu; Yong Guo; Guanqi Wu; Jun Liu (AIP Advances)
Ultrasonic motors have been widely applied and promoted due to their advantages, such as low-speed high torque, fast response, and self-locking upon power loss. However, their working principle relies on contact friction drive, and the magnitude of the applied pre-pressure directly affects their performance output. Traditionally, the magnitude of pre-pressure applied to ultrasonic motors is mainly set during manufacturing and assembly and cannot be adjusted during operation, which also affects the maximization of their performance. To address the above issues, this paper proposes the design of an electromagnet-type variable pre-pressure ultrasonic motor that adjusts the pre-pressure by controlling the driving voltage of the coil. The force and motion analysis of the core components is conducted, and the basic parameters of the electromagnetic mechanism are calculated according to design requirements. An electromagnetic-type variable pre-pressure ultrasonic motor control circuit based on speed feedback is designed, and a control method for the variable pre-pressure motor is proposed. Magnetic circuit simulation is conducted, and internal structural size parameters are optimized. Finally, experiments are conducted on the processed prototype. The results show that using the electromagnet-type variable pre-pressure ultrasonic motor can achieve speed adjustment through pre-pressure adjustment, maintaining a wide adjustment range under heavy load conditions, which is conducive to achieving a better low-speed high-torque output.